The Effect of Doing Regular Moderate Physical Exercise on Some Hormones and Oxidative Stress Indicators Levels in Women - Ali S. Mahmoud; Khalid Shaalan Sahab; Mohammed Asaad Mahdi (ASJ - Academic Science Journal, 2023)
Physical training is an indispensable part for good health and is beneficial factor of lifestyle. Physical exercises can lower the severity of some diseases, such as the risk of endocrine, cardiovascular, immune system diseases and many others. The study aimed to study the effect of continuous moderate physical exercises on the levels of some hormones and oxidative stress indicators in young women by the determination of follicle‑stimulating hormone "FSH", Luteinizing hormone "LH", Prolactin, Progesterone, Estradiol, Testosterone, and Thyroid stimulating hormone "TSH" and oxidative stress state (estimation total antioxidant capacity "T-AOC" and malondialdehyde "MDA") in serum of young women who do constant moderate physical training and compared with same parameters for young women who are not making constant moderate physical training. The study was conducted in College of Physical education and sports sciences and College of Science, University of Diyala, for the period 1-30 May 2022. The study includes 160 unmarried young women, 76 girls have been chosen from College of Physical education and sports sciences as group 1 (do regular moderate Physical exercise) and 84 girls have been chosen from College of Science as control group "group 2" (non-make physical exercise), the ages of two groups were in range18-23 yrs. The samples of blood were collected from each participant during the morning of the second day of menstruation. Hormones levels were measured by cobas E411 analyzer (Roche, Germany) for hormones determination. The total antioxidant capacity (T-AOC) was measured by using T-AOC Elisa Kit (Radix, England). Malondialdehyde (MDA) was measured by using Beuge and Aust method. The results of FSH, Estradiol, Prolactin and T-AOC have been showed differences with significant elevation(P<0.05) between group1 in comparison with the group2, while LH, Progestegrone, TSH, and MDA were higher in group1 compared with group2 but without significant differences (P> 0.05). Testosterone was lower in group1 compared to group2 but also without significant differences (P>0.05). The regular moderate physical exercises in women may contribute to total increase of sex female hormones, in addition there is an increase in total capacity of anti-oxidants and that may decrease free radicals’ formation.